La organización del archivo y su incidencia en las funciones del personal de la secretaría general técnica de la universidad metropolitana - Quiroz Cedeño, Maricela (2015)
This research project: was held at the Headquarters of the Metropolitan University of Ecuador. It aims to meet effectively and efficiently the exigencies the university community (authorities, teachers and students) in access to information. The Technical Secretariat is the department that generates and receives several submissions, mainly from students and teachers. It seeks to ensure a perfect preservation of documents and the order of the file, keeping in reserve, under specific information security processes and key to the development of the institution. All this taxed to provide a direct benefit both to those seeking information and those who administer it. Chapter one describes the background of the research project, the existing problems, the objectives pursued, the hypothesis and to identify the variables. Chapter two, what are the theoretical references on the document management and document handling in all its variations. Chapter three describes in full the research conducted, the research methods, techniques and tools for data collection, the place where the research was conducted, the treatment given to information processing and analysis data and presentation of results. A proposal to resolve the problems described above and checking the hypothesis presented in the final chapter…………